The circular model of personality traits structure in Goldberg’s proposal - Strus, Włodzimierz; Cieciuch, Jan; Rowiński, Tomasz (Studia Psychologica: Theoria et praxis, 2011)
The Five Factors Model of personality (Digman, 1990) is one of the most prominent taxonomies of traits. Many of the empirical studies supporting the FFM led McCrae (2009) to the comparison of the FFM to the physics of personality. However, researchers have faced some problems in relation to the FFM, both theoretical and methodological. The main reason of those problems could reffers to the organization of lower level personality traits. The FFM assumes the hierarchical structure of traits. It means that all five basic personality dimension have their own facets, independent from each other. the Abridged Big Five Dimensional Circumplex (AB5C) proposed by Hofstee, de Raad and Goldberg (1992) is a competitive model describing the personality traits structure as circularly organized. Lower-level traits are characterized by loadings on a subset of two from five factors in AB5C model. Each pair of the Big Five factors shape a circumplex that incorporates facets (lower-level traits). This way AB5C model consists of 10 twodimensional circumplexes that could be treated - in a metaphoric language - as a kind of “periodic table” of personality traits (Hofstee, et al., 1992). The article presents the main assumptions of AB5C model operationalized by IPIP- 45AB5C questionnaire, with the emphasis on differences between hierarchical and circular models of personality structure.